ANALYSIS OF THE RELATIONSHIP OF INCOME WITH THE PROPORTION OF HOUSEHOLD FOOD EXPENDITURE OF RICE FARMS IN GAMPONG ALUE MERBAU, LANGSA CITY - Hanisah Hanisah; Silvia Anzitha; Fitri Lia Ningsih; Rini Mastuti (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
The purposes of this research were 1) to analyze the household income of rice farmers in Gampong Alue Merbau, 2) to analyze the proportion of household food expenditures for rice farmers in Gampong Alue Merbau, 3) to analyze the relationship between income and the proportion of household food expenditures for rice farmers in Gampong Alue Merbau. This research was conducted in Gampong Alue Merbau, East Langsa District, Langsa City. The analytical methods used are rice farmer household income analysis, rice farmer household food expenditure proportion analysis, and Pearson Correlation analysis. The results showed that the average household income of rice farmers was Rp 2,898,804/month. The average proportion of household food expenditure is 52%. Income with the proportion of food expenditure has a significant relationship. The correlation coefficient value is -0.579, which indicates a moderate relationship. The correlation coefficient value in the analysis results is negative, which means that income and the proportion of food expenditure have an opposite relationship. If the income is high, the proportion of food expenditure is low; if the income is low, the proportion of food expenditure is high.